(untitled) - Nagle, Thomas T. (Upper Saddle River, NJ, 2002)
For Pricing Strategy or Pricing and Product Policy courses in MBA and/or advanced undergraduate marketing courses The Strategy and Tactics of Pricing provides a comprehensive, practical, step-by-step guide to pricing analysis and strategy development.
Keywords: Marketing,Pricing; Decision making